INTERAKSI ETNIS JAWA DAN ETNIS SUNDA DI KAMPUNG PASIR LEUTIK - Abdul Malik, Aminullah; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Differences in cultural backgrounds, languages, and habits cause various obstacles when communicating between Javanese and Sundanese, but with the interaction between the two, it can create an increasingly harmonious relationship between other. Each strangers has his own way of being able to adapt to his new environment, as well as the host culture, of course, having their own views of the newcomers when initial interactions occur. This study aims to find out how the interaction between Javanese and Sundanese Ethnics in the Pasir Leutik village and also to find out what obstacles are experienced by ethnic Javanese individuals living in the Pasir Leutik village, through a phenomenological approach. This research uses the foundation of (Intercultural Communication Theory) and (Interaction Adaptation Theory) by Judee Burgoon. Collection techniques used in this study were in-depth interviews with research subjects of five Javanese ethnic respondents who lived permanently in the Pasir Leutik village. This research concludes (a) There are obstacles that arise in the process of intercultural interaction between ethnic Javanese and Sundanese in the Pasir Leutik village such as language, cultural norms, negative prejudice and ridicule. Language barriers become a major barrier because language is the main means of communication, but language differences can cause attraction for ethnic Javanese individuals to make intercultural communication. (b) Every ethnic Javanese individual has their own way of being able to interact and adapt to the host culture, besides that another thing found is that the intensity of the time span in the new residential environment affects the extent to which the individual is able to adapt to his new environment.